SOFTWARE FOR DESIGNING PARALLEL APPLICATIONS - M. K. Bouza; O. M. Kondratjeva (Informatika)
The object of research is the tools to support the development of parallel programs in C/C ++. The methods and software which automates the process of designing parallel applications are proposed.